Neuroscience and Christian formation - Maddix, Mark A., 1965-; Blevins, Dean Gray (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
Why a text on neuroscience and Christian formation? Simply put, we need one that represents the range of possible intersections for today and into the future. In recent years, neuroscience's various fields of study have influenced our understanding of the person, memory, learning, development, communal interaction, and the practice of education.The book serves as an introductory textbook for Christian education/formation professors to use in Christian education or Christian formation courses at the College or Seminary level. The book is designed to provide an overview of how current research in neuroscience is impacting how we view Christian education and formation with particular attention given to faith formation, teaching, development, and worship The first four chapters discuss how neuroscience broadly influences Christian education and formation. Chapters five through eight explore how neuroscience informs specific formational practices, from personal meditation, to intercultural encounter, to congregational formation and worship. The last four chapters explore various aspects of neuroscience along developmental lines, The book also moves from conceptual overviews to more empirical studies late in the text. Each chapter of this book can also be read and discussed individually. Each author has provided both discussion topics, suggestions for future reading within neuroscience, and discussion questions at the end of the chapter.